Study about Graphology: A Technique for Employee Selection - Deshmukh, Tejashree (New Innovations in Economics, Business and Management Vol. 5, 2022)
Importance of Employee Selection is discussed widely by many authors till date. If we believe that the organizational success or failure is dependent on the talent pool of the employees, then we admit that Employee Selection is one of the most important areas of Human Resource Management. Thomas Stone defined Selection as "a process of differentiating between applicants in order to identify (and hire) those with a greater likelihood of success in a job". Organizations use multiple sources of information that will provide a reliable and accurate picture of the prospective employee’s potential for success on the job [1]. Though interviews of different types are the most widely used and popular technique of selection, they are prone to various biases and rator’s errors and hence, need to be supplemented with a few other techniques of selection that will enhance the probability of selecting the right candidate for the job. Graphology is one such technique and this research paper aims to study what is graphology, its role in employee selection and how it can be used as a potentially effective selection technique of the prospective employee.